2019
DOI: 10.1111/jdi.13005
|View full text |Cite
|
Sign up to set email alerts
|

Twincretin as a potential therapeutic for the management of type 2 diabetes with obesity

Abstract: Unimolecular peptide‐based dual agonists against glucagon‐like peptide‐1 receptor (GLP‐1R) and glucose‐dependent insulinotropic polypeptide receptor (GIPR) have been gaining much attention recently as novel antidiabetic agents that can potentially control glycemia and bodyweight. Although GLP‐1 and GIP both enhance insulin secretion and subsequently ameliorate postprandial glucose excursion, most research has focused on GLP‐1R as a therapeutic target for type 2 diabetes. This is partly because the effects of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
0
17
0
3
Order By: Relevance
“…A synergistic action in which glucagon receptor activation enhances energy expenditure whilst GLP-1 receptor agonists reduce calorie intake and both GLP-1/GIP potentiate the incretin effect to modulate the diabetogenic effect of glucagon agonists. Two triple agonists are currently in early stages of clinical trials with no yet published clinical trial data [48]. However, preclinical studies of these drugs demonstrate supportive results in rodent and mice models [53][54][55], and we await further clinical trial data with anticipation.…”
Section: Glp-1/gip/glucagon Receptor Triple Agonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…A synergistic action in which glucagon receptor activation enhances energy expenditure whilst GLP-1 receptor agonists reduce calorie intake and both GLP-1/GIP potentiate the incretin effect to modulate the diabetogenic effect of glucagon agonists. Two triple agonists are currently in early stages of clinical trials with no yet published clinical trial data [48]. However, preclinical studies of these drugs demonstrate supportive results in rodent and mice models [53][54][55], and we await further clinical trial data with anticipation.…”
Section: Glp-1/gip/glucagon Receptor Triple Agonistsmentioning
confidence: 99%
“…Several clinical trials have observed significant weight loss associated with the use of these drugs from 2.1 to 3.1 kg [46,47]. Encouragingly, there are several ongoing and unreported preclinical, phase I/II trials investigating drugs utilising this dual mechanism of action [48].…”
Section: Glp-1/glucagon Receptor Dual Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the physiological point of view, it is meaningful to compare the functions of three kinds of related hormones, which are GLP-1, gastric inhibitory polypeptide (GIP) and glucagon. These factors seem to have various effects on several organs, such as the brain, gastrointestinal tract, pancreas, liver, adipose tissue and bone [17]. Among them, GLP-1 and GIP is a pair of two incretin hormones, which are secreted from the gut for the ingestion of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…However, novel findings from basic research on GLP‐1, as well as GIP, are still changing our views on how incretin‐based drugs exert their glucose‐lowering effects, and how such effects can be maximized by lifestyle modifications. In contrast, newer incretin‐based drugs, including unimolecular peptide‐based dual agonists against GLP‐1 and GIP receptors, are providing clues as to how pharmacological levels of GIP affect appetite loss and bodyweight reduction. Although it has been >100 years since the discovery of the incretin concept by Moore et al ,.…”
mentioning
confidence: 99%